المقاولة النسائية والمؤسسات الصغيرة والمتوسطة وفي الجزائر -دراسة استطلاعية- - غزال, مريم; ناصور, عبد القادر; شعباني, لطفي (جامعة الوادي University of Eloued, 2018)
استطاعت المرأة أن تشارك في الأعمال المقاولاتية وأتثبت أحقيتها في ذلك، وهذا ما أظهرته الدراسات والتقارير، بحيث توضح أهمية نشاطها في دعم الاقتصاد الوطني، وهذا من خلال خوض تجربة العمل في المشاريع الصغيرة والمتوسطة منها، حيث سعت الجزائر إلى اعتماد استراتيجيات تنمويةوسياسات تدعيميه لزيادة مساهمة المرأة وجعلها عنصرا فعالا في النسيج الاقتصادي. Women have been able to participate in the construction work and she prove that, as shown by the studies and reports, soas to demonstrate the importance of their activities in supporting the national economy through the experience of working in small and medium enterprises. Algeria has endeavored to adopt development strategies and policies to increase contribution. Making women an effective component of the economic fabric.
مقال
Keywords: المقاولة النسائية، التنمية الاقتصادية، المؤسسات الصغيرة والمتوسطة.; Women Entrepreneurship, Economic Development, Small and Medium Enterprise